"Poseł z Wołoch z obozu polskiego" - polska gazeta ulotna o batalii chocimskiej w 1621 roku (minimonografia i edycja krytyczna zabytku) = "The Envoy from Wallachia from Polish Camp" ["Poseł z Wołoch z obozu polskiego"] - Polish transitory newspaper on Khotyn battle in 1621 (minimon - Sztyber, Radosław (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The study presents a short brochure belonging to old Polish transitory newspapers andprovides with its reissue prepared after nearly four hundred years. The leaflet?s contents seems to be original for limited number of various citations or allusions included, especially in comparison with other analogical prints devoted to the Khotyn battle theme and published almost immediately after the end of the military conflict between Ottoman Empire and Polish-Lithuanian Commonwealth
Keywords: polska literatura okolicznościowa XVII wieku; Bitwa 1621 r. pod Chocimem; "Poseł z Wołoch z obozu polskiego"; Polish occasional literature of XVII century; Battle of Khotyn in 1621; "The Envoyfrom Wallachia from Polish Camp"